Analysis of the design needs and development of the AR-Kahf module for learning Arabic syntax in the Quran - Wan Amri Faizal, Wan Muhd Hafizudin; Abdul Hamid, Mohd Fauzi; Md Noor, Mohamad Lukman Al Hakim (Human Resource Management Academic Research Society, 2025)
The teaching and learning (TnL) of the Arabic language can be diversified through more innovative, interactive, and effective methods. One such approach is the implementation of Augmented Reality (AR) technology, which has emerged as a significant tool in modern educational settings. This study examines students' perspectives on the necessity of developing the AR-Kahf module for learning Arabic syntax within the Quranic framework. The study employs a Design and Development Research approach, utilizing questionnaire instruments to gather data on the need for technology-based learning materials, challenges in conventional learning approaches, students' inclination toward innovation in course instruction, and the necessity of interactive AR applications. A total of 184 undergraduate students from the Arabic Language Studies program at UniSZA, who were enrolled in the Ibn Hisham Syntax Text Study Course, served as respondents for the questionnaire. The collected quantitative data were analyzed using the Statistical Package for Social Science (SPSS) to obtain mean values and standard deviations. The results indicate that students perceive the development of the AR-Kahf module as necessary. This module should be established as an alternative pedagogical approach for teaching Arabic syntax in the Quran, integrating interactive and visual elements to enhance students' comprehension and engagement with the complex sentence structures